2021
DOI: 10.1002/ente.202100570
|View full text |Cite
|
Sign up to set email alerts
|

Design Predictions of n–n Heterojunction Based Photoanode for Efficient Unbiased Overall Solar Water Splitting

Abstract: There are multiple requirements for maximizing the efficiency of photoelectrochemical overall water splitting using a single n‐type semiconducting photoanode. Many visible‐light‐responsive photoanode materials have been developed but overall water splitting by such materials without external bias has hardly been demonstrated. Herein, the aim is to scale the impact of performance improvement by an n–n heterojunction photoanode comprising an n‐type thin modification surface layer over an n‐type photon absorber, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, Ta 3 N 5 with the thinner IrO x layer showed the most negative onset potential, 0.7 V versus RHE. Our previous study reported that the onset potential of the OER shifted negatively as the electrocatalyst layer thickness decreased because of favorable upward band bending at the modification layer/ photoelectrode interface, 39 consistent with the current experimental result. Nevertheless, the onset potential is still substantially more positive compared to a flatband potential of ∼0 V versus RHE.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…On the other hand, Ta 3 N 5 with the thinner IrO x layer showed the most negative onset potential, 0.7 V versus RHE. Our previous study reported that the onset potential of the OER shifted negatively as the electrocatalyst layer thickness decreased because of favorable upward band bending at the modification layer/ photoelectrode interface, 39 consistent with the current experimental result. Nevertheless, the onset potential is still substantially more positive compared to a flatband potential of ∼0 V versus RHE.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…The fundamental mechanism governing charge separation in a photoelectrode is generally discussed using a one-dimensional (1D) energy-band model (Figure S1a). In this model, the Schottky junction at the semiconductor/electrolyte interface and the ohmic contact at the semiconductor/substrate interface give rise to the energetics that drive charge separation. Such energetics are denoted as “bulk energetics” because they drive the migration of charge carriers across the bulk of a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54] For example, Ta3N5-based n-n heterojunctions have been developed by many groups. 48,[55][56][57] Recently, our group reported a guideline for the design of Ta3N5-based n-n heterojunctions. 58 However, there is little research on Ta3N5based p-n heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…48,55–57 Recently, our group reported a guideline for the design of Ta 3 N 5 -based n–n heterojunctions. 58 However, there is little research on Ta 3 N 5 -based p–n heterojunctions. 59,60…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation